Floristic Diversity and Natural Regeneration Status of Entoto Mountain and the Surrounding Area in Addis Ababa, Ethiopia - Ergua Atinafe; Ephrem Assefa; Birhanu Belay; Yemenzwork Endale; Talemos Seta (International Journal of Forestry Research)
The study was carried out at Entoto Mountain and its surrounding area, about 10 km north of the center of Addis Ababa. The purpose of this study was to assess the floristic composition and regeneration status of woody species and recommend further conservation methods. Ten transect lines were laid from south-north at 1 km interval. Along these transect lines, 62 sample plots of 400 m2 (20 m × 20 m) were laid at 1 km interval. A total of 179 plant species belonging to 107 genera and 60 families were recorded. Asteraceae (30 species) was the most dominant family. Of 179 plant species, 73 were naturally regenerated woody species representing 48 genera and 34 families. Herbs account for the largest growth form (91, 50.84%), indicating the fact that disturbance favors herb species. For the analysis of vegetation diversity, woody species composition, and density, the study area was classified into five land-use types. Of the five land-use types, degraded land-use type had low species diversity and evenness (1.48 and 0.295), and it had a low density of economically and ecologically important larger trees. However, the density of seedlings and saplings showed the normal regeneration status for the herbs and shrubs. Therefore, responsible stakeholders should give high priority for the conservation of ecologically and economically important large trees using appropriate conservation methods in the study area.